Effects of prophylactic knee bracing on knee joint kinetics and kinematics during netball specific movements. (January 2017) - Sinclair, Jonathan K.; Vincent, Hayley; Richards, Jim D.
Abstract: Objective: To investigate the effects of a prophylactic knee brace on knee joint kinetics and kinematics during netball specific movements. Design: Repeated measures. Setting: Laboratory. Participants: Twenty university first team level female netball players. Outcome measurements: Participants performed three movements, run, cut and vertical jump under two conditions (brace and no-brace). 3-D knee joint kinetics and kinematics were measured using an eight-camera motion analysis system. Knee joint kinetics and kinematics were examined using 2 × 3 repeated measures ANOVA whilst the subjective ratings of comfort and stability were investigated using chi-squared tests. Results: The results showed no differences (p > 0.05) in knee joint kinetics. However the internal/external rotation range of motion was significantly (p < 0.05) reduced when wearing the brace in all movements. The subjective ratings of stability revealed that netballers felt that the knee brace improved knee stability in all movements. Conclusions: Further study is required to determine whether reductions in transverse plane knee range of motion serve to attenuate the risk from injury in netballers. Highlights: First study to look at prophylactic knee bracing in netballers. Prophylactic bracing reduced knee relative internal/external range of motion. Netballers susceptible to knee pathology may wish to use prophylactic knee bracing.